2022
DOI: 10.3390/ani12182404
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Death Investigations of Dog Bite Injuries in 31 Cats

Abstract: Animal bite injuries are common in free-ranging cats in Taiwan, and most fatal animal bite events are presumed to be caused by dogs. However, speculation regarding animal abuse may occur when carcasses with prominent injuries are found by members of the general public. Local animal protection offices and veterinary clinicians sometimes face difficulties in convincing these individuals by identifying specific features of dog bite injuries in cat carcasses. Therefore, the present study analyzed injury patterns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Dog bites are common occurrences that can cause significant injury. The most common characteristics of dog bites include blunt force trauma due to their powerful jaw closure and teeth with rounded apices, a combination of tearing and compressive forces, lacerations or avulsions of the skin and deeper tissues and puncture wounds [ 9 - 10 ]. Puncture wounds may not be present in some cases due to the rounded apices of their teeth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dog bites are common occurrences that can cause significant injury. The most common characteristics of dog bites include blunt force trauma due to their powerful jaw closure and teeth with rounded apices, a combination of tearing and compressive forces, lacerations or avulsions of the skin and deeper tissues and puncture wounds [ 9 - 10 ]. Puncture wounds may not be present in some cases due to the rounded apices of their teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Puncture wounds may not be present in some cases due to the rounded apices of their teeth. Furthermore, dog bites often have an "iceberg" feature, with relatively minor skin lesions concealing important lacerations and injuries of deeper tissues and organs [ 10 ]. The "hole-and-a-tear" effect is also often present in dog bites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequencing method established in this study for whole dog mtDNA might be applicable in forensic cases. Recently, in their study, Hsiou et al reported that the resequencing performed for dog mtDNA obtained from a bite wound proved valuable in identifying perpetrators in cat-killing cases [31]; however, they also admitted that the method requires improvement, since the target region was limited and only 100 bp in dog mitochondrial cytochrome b was examined [32]. In this respect, the method has the advantage of being able to resequence whole mtDNA, which is expected to improve the sensitivity and specificity factors of DNA testing.…”
Section: Discussionmentioning
confidence: 99%